The study of labor conditions from a geographical perspective. A review of research in Spain - Montesinos-Ciuró, Eduard (Revista de Estudios Andaluces, 2023)
A state of the art on the labor conditions of the population from a geographical perspective is presented, with emphasis on what happens in Spain. The secondary sources available in the main scientific search engines (Google Scholar) and the databases of Spanish geography journals (Dialnet) are reviewed based on the keywords precarious work and labor precarity. The approximately fifty texts analyzed are grouped into three approaches: primary labor market, secondary labor market and a synthesis which is proposed to be called labor geography as in the Anglo-Saxon context. It is confirmed the limited development of this research agenda in the Spanish geography and the need for its implementation from a critical conception of the discipline.